Lethargy as an initial symptom of intussusception secondary to Meckel's diverticulum in a 2.5 year-old girl: Case report. (August 2021) - Badour, Maysaa; Hammed, Ali; Baqla, Sameer
Abstract: Introduction: and importance: Intussusception is one of the most common causes of acute abdomen and surgical morbidities in the childhood. In a paediatric presentation of intussusception due to Meckel's diverticulum there may be acute onset of abdominal pain, vomiting or painless red currant stools. However, Lethargy has been described as a rare presenting symptom Case presentation: We present a case of 2, 5 – year old female complained of acute alternation in consciousness followed by continuous vomiting two days later. Clinical discussion: Her neurological examination showed a lethargic child, not reactive and hypotonic. Her past medical history was unremarkable. Abdominal ultrasonography was compatible with ileocolic intussusception. The necrotic bowel and diverticulum were resected, followed by anastomosis of the viable bowel segments. postoperatively the infant recovered dramatically. Conclusion: Although lethargy is a rare presenting symptom of Intussusception, it should be kept as a differential diagnosis when a child presents with acute onset of drowsiness with or without abdominal symptoms. Highlights: Intussusception is one of the most common causes of acute abdomen and surgical morbidities in the childhood. It should be kept as a differential diagnosis when a child presents with acute onset of drowsiness. Early diagnosis could save grave complications and improve the prognosis.